"Vivir Bien": A Discourse and Its Risks for Public Policies — The Case of Child Labour and Exploitation in Indigenous Communities of Bolivia (Alternautas, 2015)
The Código Niño Niña Adolescente (CNNA) (the “Boy, Girl and Adolescent Code”) was amended and approved in 2014 amid critical and supporting opinions. For the first time in Bolivia and Latin America something unprecedented occurred: a state had defined its policy reforms in negotiation and dialogue with representatives of working children and adolescents (Niños, Niñas y Adolescentes Trabajadores, NATs). In 2005, the government of Evo Morales started, as part of its political strategy, to work together with social, indigenous and peasant organizations. Child labour policies were not excluded from this new model. This way, the participation of child workers in meetings with the president and ministers evoked recognition by the population and media. However, gaps in definitions of labour, exploitation, educational work and others are still a pending issue. As for now, the reduction of the minimum age for employment has attracted international attention and the International Labour Organizationm has already expressed its disagreement. However, it is important to warn about the danger of the existence of discursive backgrounds, in this case the "Vivir Bien", in public policy as a limiting factor in this and other important issues in development programs.